Differences in eating disorder symptomatology between athletes and non-athletes - Gonidakis, F.a d; Liakopoulou, E.b; Psychountaki, M.c; Barsou, E.a; Soldatos, K.a (Archives of Hellenic Medicine, 2008)
OBJECTIVE: The aim of this study was to investigate possible differences in eating disorder symptomatology between a group of athletes and a group of university students as well as to investigate the risk factors for developing of eating disorders symptomatology in females. METHOD: The EAT-26, BDI, STAI and SPAS (trait) questionnaires were administered to 60 adult athletes (27 female and 33 male) and 60 non-athlete university students (40 female and 20 male). Each subject was asked to indicate on a series of 12 male and 12 female human figures those that they considered as the ideal male and female body, and the figure that in their mind resembled most their own body. The body mass index (BMI) was calculated for each subject. RESULTS: Male athletes scored higher in the oral control dimension of EAT-26 than male non athletes. Female athletes also perceived their body as leaner than female non-athletes did (P=0.003), although there was no statistically significant difference between the BMI of the two groups. A subgroup of women (n=7, 10.4%) who had disordered eating attitudes (EAT >20) chose leaner ideal female figures and also scored higher on the BDI, STAI trait and SPAS questionnaires. Younger age (P=0.04), being an athlete (P=0.03) and SPAS score (P=0.02) were found in logistic regression analysis to influence significantly the risk of development for developing disordered. CONCLUSIONS: There were only minor differences in eating disorder measurements between athletes and non-athletes. A small group of young women who are preoccupied with their physical appearance and are involved in athletic activities appears to run a greater risk for developing disordered. Copyright © Athens Medical Society.
Keywords: Adult; article; athlete; body mass; controlled study; eating disorder; Feeding Behavior; Female; human; major clinical study; Male; questionnaire; Risk factor; sex difference; symptomatology